Evaluation of common genetic variants in pre‐microRNA in susceptibility and prognosis of esophageal cancer. Issue 1 (12th June 2012) - Umar, Meenakshi; Upadhyay, Rohit; Prakash, Garima; Kumar, Shaleen; Ghoshal, Uday Chand; Mittal, Balraj; Angel, Joe
Abstract Genetic variants in micro‐RNAs (miRNA) have been shown to affect progression, diagnosis, and prognosis of various malignancies; however, their role in esophageal squamous cell carcinoma (ESCC) susceptibility is controversial. Therefore, we aimed to determine role of common genetic variants in cancer related pre‐miRNA in susceptibility and survival outcome of north Indian ESCC patients. We genotyped four common polymorphisms in pre‐miRNA: mir‐196a‐2C>T, mir‐146aG>C, mir‐499T>C, and mir‐423C>A in 289 incident ESCC cases (including 153 follow‐up cases) and 309 controls using PCR/PCR RFLP‐based methods. Binary logistic regression was applied for risk estimation, while Kaplan–Meier and Cox Regression tests were performed for survival analysis. We observed that none of the pre‐miRNA genetic variants were associated with ESCC or its clinical phenotypes independently, however, combined risk genotypes of four pre‐miRNA polymorphisms increased risk of ESCC in dose–response manner (Ptrend = 0.011). Specifically, patients with 2–4 risk genotypes of pre‐miRNA polymorphisms had 1.4‐fold higher risk of ESCC compared to patients with 0–1 risk genotypes (OR = 1.43, 95% CI = 1.02–1.09, P‐value = 0.037). The risk was more pronounced in ESCC cases with upper‐third esophageal tumors. Moreover, cumulative but not independent effect of risk genotypes of pre‐miRNA polymorphisms was observed on survival outcome of ESCC patients. Cases with 2–4 risk genotypes had significantly lower median survival (11.60 vs. 30.2 months) and 2.3‐fold greater hazard of death compared to patients with 0–1 risk genotypes. In conclusion, the four studied common pre‐miRNA polymorphisms cumulatively affect susceptibility and survival of ESCC patients in north Indian population. © 2012 Wiley Periodicals, Inc.